Comparative Analysis of Tear Composition in Humans, Domestic Mammals, Reptiles, and Birds - Raposo, Ana Cláudia; Portela, Ricardo Dias; Aldrovani, Marcela; Barral, Thiago Doria; Cury, Dayse; Oriá, Arianne Pontes (Frontiers in Veterinary Science, 2020)
Tears are an important component of the ocular surface protection mechanism and are in close contact with the corneal epithelium and the environment. Their composition is well-known in humans; however, there are few investigations on the composition and function of tears in reptiles, birds and others mammals, which would elucidate the mechanisms governing the maintenance of ocular homeostasis. In this work, electrophoretic profiles and an evaluation of total protein, albumin, urea, glucose, and cholesterol concentrations in tears of semi-aquatic, terrestrial, and marine reptiles (Caiman latirostris, Chelonia mydas, Caretta caretta, Eretmochelys imbricata, Lepidochelys olivacea, and Chelonoidis carbonaria), birds (Tyto furcata, Rupornis magnirostris and Ara ararauna), and mammals (Equus caballus and Canis lupus familiaris) were apresented. Human tear components and respective blood serum samples were used as references. The electrophoretic analysis revealed similarities whithin same Classes. The results of the tear–blood serum relationship and the comparison to human tear components showed particularities that are potentially derived from a homeostatic response to the environment. When the tear compositions of animals belonging to different ecological clusters were compared, marked differences were observed in total protein and urea concentrations. Thus, reptile, bird, and mammalian tears are complex fluids with differing concentrations of biochemical components that are potentially a result of the animals' adaptation to different environments.